Poland : Directions in Regional Policy - World Bank (Washington, DC, 2013)
Poland along with seven other Central European and Baltic countries, joined the European Union (EU) on May 1, 2004. This was a historical event, marking the country's final reintegration with the rest of Europe, and the importance of this from a geopolitical point of view is undeniable. For Poland and the other new member countries, the distinction between external and internal convergence is less important from the EU perspective as virtually all regions within these countries have income levels significantly below the EU average and are eligible for financial support from the union. Thus, these countries have considerable discretion in how the EU financial support is allocated among its constituent regions and among various programs. This is done according to National Development Plans (NDPs) and Community Support Frameworks (CSFs) agreed with the EU. This report discusses regional income disparities and policies in Poland and the likely impact on these on European Union (EU) accession and provides recommendations for the successor National Development Plan (NDP) currently under preparation for the next EU budget period (2007-13). The report is organized as follows: Section 2 discusses external and internal convergence in Poland during the transition period and analyses the sources of regional income disparities; Section 3 discusses the likely impact of EU accession and Section 4 examines regional policy in Poland.